FAKTOR YANG MEMPENGARUHI MOTIVASI WISATAWAN NUSANTARA BERKUNJUNG KE PANTAI PASUT, TABANAN - Hadi, Aneisya Audeslina; Sudana, I Putu; Sasrawan Mananda, IGPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p07, 2024)
This research focuses on the factors that influence the motivation of tourists to visit Pasut Beach, a popular tourist attraction in Tabanan Regency that gained attention on social media in 2018. The study involved 130 domestic tourists who had previously visited Pasut Beach. Data was collected through observation, questionnaires, interviews, literature review, and documentation. Factor analysis was conducted using SPSS for Windows Version 25 to analyze the data. The findings revealed that the majority of respondents were female, aged between 17 and 25 years old, unmarried, had a high school diploma or equivalent education, and were students from East Java. Most tourists spent less than IDR 100,000 during their visit. Common tourist activities included taking selfies, using motorized vehicles, and obtaining information through social media platforms. Six motivating factors for visiting Pasut Beach were identified: self-fulfillment, relationship, escape from routinity and relaxation, romance moment, family bonds, and prestige. Additionally, three attracting factors for visitors were identified: product and facilities, information about the destination, and natural scenery. The study concluded that “self-fulfillment” was the most influential factor motivating domestic tourists to visit Pasut Beach, while the availability of diverse “product and facilities” was the dominant factor attracting them.